Predictor-based phase-lead active disturbance rejection control design for industrial processes with input delay - Li, Xiaomeng; Hao, Shoulin; Liu, Tao; Yan, Bin; Zhou, Yongzhi (Frontiers in Control Engineering, 2022)
For industrial processes subject to input delay, a predictor-based phase-lead active disturbance rejection control (ADRC) scheme is proposed in this article for improving disturbance rejection performance by introducing a phase-lead module for feedback control. First, an extended state observer (ESO) in combination with a generalized delay-free output predictor is presented to estimate the delay-free system state together with load disturbance lumped with process uncertainties. To reduce the phase lag caused by not only ESO but also the delay-free output predictor, a phase-lead module is then added into the disturbance observation channel so as to expedite disturbance estimation and thus improve the disturbance rejection performance. Consequently, the ESO gain vector and feedback controller are analytically designed by specifying the desired poles for the observer and the closed-loop system, respectively. Moreover, a digital implementation of the proposed scheme is presented to facilitate the practical applications, followed by a robust stability analysis of the closed-loop system based on the small gain theorem. Illustrative examples from the literature are used to demonstrate the effectiveness and merits of the proposed method over the existing methods.